Endovascular Treatment of Intracranial Aneurysms: Initial Experience in a Low-Volume Center. Issue 1 (6th May 2020) - Gudelj, Maxime; Bruyère, Pierre-Julien; Tebache, Malek; Collignon, Laurent; Lubicz, Boris
Objective: Endovascular treatment (EVT) is the first-line treatment for ruptured and unruptured intracranial aneurysms (IA). EVT may be performed by interventional neuroradiologist (INR) with different levels of experience. This study aimed at evaluating clinical and anatomic results of IA embolisations performed by a INR with a short experience. Materials and Methods: Within a 26-month period, 35 IA embolisations were managed by a young INR, 26 of these IA being ruptured. Different EVT techniques were used: coiling alone, stent-assisted coiling and remodeling techniques. Initial angiographic results, clinical outcomes and mid-term anatomic results were evaluated. Results: Out of 35 procedures, there were seven per-procedural complications leading to one ischemic stroke and one death. Immediate post-procedural complete occlusion was obtained in 91% of procedures (32/35). Good clinical results (modified Rankin Scale Score of 0 or 1) were obtained in 79% of patients (26/33). In a mean follow-up time of 9.5 months, stable occlusion was shown in 88% of IA (21/24). Conclusion: This study suggests that IA embolisation may be performed by a recently trained INR with good clinical and anatomical outcomes.